Evaluation of diagnostic accuracy of biomarkers of inborn errors of metabolism in sick neonates: A prospective observational study - N.B. Mathur; Kaushaki Shankar; Seema Kapoor; Bijo Varughese (Elsevier, 2021)
Objective: To evaluate the diagnostic accuracy of a set of predefined biomarkers (index test) in diagnosing diseases targeted in expanded newborn screening (ENS) namely organic acidemias, fatty acid oxidation disorders, and amino acid disorders. Methods: This was a prospective study. The study population consisted of out born neonates admitted to a teaching hospital for the study duration of 12 months. The presence of any of the predefined biomarkers was considered index test positive. Tandem Mass Spectrometry on dried blood samples along with urinary gas chromatography mass spectrometry (GCMS) was considered the gold standard (reference test) for diagnosis of diseases targeted in ENS. Results: A total of 783 out born neonates were evaluated using the index test and 30 tested positive, out of which, 18 were reference test positive. All index test negative neonates (n = 30) were reference test negative. The index test had a sensitivity of 100%, specificity of 71.42%, with 60% positive predictive value and 100% negative predictive value. The area under ROC curve for the index test was 80%. Conclusions: In the absence of universal screening programs, the evaluated biomarkers (index test) can be useful to decide which cases should be selectively referred for mass spectrometric techniques. Further multicentric studies are required to assess these biomarkers before incorporating them in national programs.